SERVICE QUALITY, SATISFACTION, CONTINUOUS USAGE INTENTION, AND PURCHASE INTENTION TOWARD FREEMIUM APPLICATIONS: THE MODERATING EFFECT OF PERCEIVED VALUE - Suryawirawan, Okto Aditya; Suhermin, Suhermin; Shabrie, Wiwiek Srikandi (Fakultas Ekonomi dan Bisnis, UNTAN, 2022)
This study aimed to analyze factors that could influence continuous usage intention on freemium applications and purchase intention of premium services among students. Non-probability purposive sampling was used to determine the respondent. The criteria for the sample for this study were students who used freemium applications. Data were analyzed using Partial Least Square. The results confirmed that only reliability and responsiveness positively impacted customer satisfaction among the service quality dimensions, while assurance and empathy showed no effect. Only assurance and responsiveness were found to affect continuous usage intention positively, while empathy and reliability were found to have no effect. There was no evidence of the effect of the dimensions of service quality on purchase intention. Perceived value failed to moderate the effect of service quality on customer satisfaction. While there was a significant positive impact of customer satisfaction towards continuous usage intention, no effect has been found towards purchase intention. Continuous usage intention was confirmed to have a positive impact on purchase intention.JEL: O32, M31, L11ABSTRAKTujuan dari penelitian ini adalah untuk menganalisis faktor-faktor yang dapat mempengaruhi continuous usage intention dan purchase intention pada aplikasi yang memiliki layanan premium pada mahasiswa. Non-probability purposive sampling digunakan untuk menentukan jenis responden. Kriteria sampel pada penelitian ini adalah mahasiswa yang menggunakan aplikasi freemium. Data dianalisa menggunakan Partial Least Square. Hasil menunjukkan bahwa diantara dimensi service quality, hanya reliability dan responsiveness yang berpengaruh positif terhadap customer satisfaction sedangkan assurance dan empathy tidak berpengaruh. Hanya assurance dan responsiveness yang ditemukan berpengaruh positif terhadap continuous usage intention sedangkan empathy dan reliability ditemukan tidak berpengaruh. Seluruh dimensi service quality ditemukan tidak berpengaruh terhadap purchase intention. Perceived value tidak mampu memoderasi pengaruh service quality terhadap customer satisfaction. Customer satisfaction ditemukan berpengaruh positif terhadap continuous usage intention tetapi tidak terhadap purchase intention. Continuous usage intention ditemukan berpengaruh positif terhadap purchase intention.Kata Kunci: kualitas layanan, persepsi nilai, kepuasan, niatan